Synthesis, structures and urease inhibitory activity of cobalt(III) complexes with Schiff bases. Issue 2 (15th January 2016) - Jing, Changling; Wang, Cunfang; Yan, Kai; Zhao, Kedong; Sheng, Guihua; Qu, Dan; Niu, Fang; Zhu, Hailiang; You, Zhonglu
Graphical abstract: Abstract: A series of new cobalt(III) complexes were prepared. They are [CoL 1 (py)3 ]·NO3 (1 ), [CoL 2 (bipy)(N3 )]·CH3 OH (2 ), [CoL 3 (HL 3 )(N3 )]·NO3 (3 ), and [CoL 4 (MeOH)(N3 )] (4 ), where L 1, L 2, L 3 and L 4 are the deprotonated form of N ′-(2-hydroxy-5-methoxybenzylidene)-3-methylbenzohydrazide, N ′-(2-hydroxybenzylidene)-3-hydroxylbenzohydrazide, 2-[(2-dimethylaminoethylimino)methyl]-4-methylphenol, and N, N ′-bis(5-methylsalicylidene)- o -phenylenediamine, respectively, py is pyridine, and bipy is 2, 2′-bipyridine. The complexes were characterized by infrared and UV–Vis spectra, and single crystal X-ray diffraction. The Co atoms in the complexes are in octahedral coordination. Complexes1 and4 show effective urease inhibitory activities, with IC50 values of 4.27 and 0.35 μmol L −1, respectively. Complex2 has medium activity against urease, with IC50 value of 68.7 μmol L −1 . While complex3 has no activity against urease. Molecular docking study of the complexes with Helicobacter pylori urease was performed.